Efficient native strains of rhizobia improved nodulation and productivity of French bean (Phaseolus vulgaris L.) under rainfed condition - Puthan Purayil Athul; Ranjan Kumar Patra; Debadatta Sethi; Narayan Panda; Sujit Kumar Mukhi; Kshitipati Padhan; Sanjib Kumar Sahoo; Tapas Ranjan Sahoo; Satyabrata Mangaraj; Shriram Ratan Pradhan; Sushanta Kumar Pattanayak (Frontiers in Plant Science, 2022)
Biological nitrogen fixation is the most important eco-friendly approach to nitrogenous fertilizer management in the rhizosphere. Rhizobium is considered the most important symbiotic N-fixing microorganism. Native strains of Rhizobium perform better than the non-native strains by getting ambient conditions for growth and proliferation. Native strains enhance the soil fertility and productivity of pulses. The study was carried out in three phases, i.e., pot experiment, field experiment, and farmers’ field demonstrations. In a pot experiment, two isolated rhizobia were inoculated to seeds of French bean (Phaseolus vulgaris) and applied with and without lime to evaluate crop growth, photosynthetic activity, and nodule characteristics of the target crop. In the field, strains were inoculated to seeds of French bean, which received different combinations of inputs— inorganic fertilizers, lime, and boron— to study the influence of native stains on crop productivity and agronomic efficiency. In comparison to non-limed packaging, the amounts of chlorophyll a, chlorophyll b, total chlorophyll, and chlorophyll a:b were, respectively, 13% to 30%, 1% to 15%, 10% to 27%, and 1% to 20% greater in limed packages. In limed packages compared to non-limed packages, the root length, biomass, density, and growth rate were increased by 16% to 17%, 36% to 52%, 38% to 49%, and 36% to 52%, respectively. In contrast to non-limed packages, limed packages had nodule attributes like the number of nodules per plant and nodular weight, which were 28% to 41% and 33% to 37% greater, respectively. Inoculation of native rhizobia strains with liming to acid soil increased 46% to 72% of leaf nitrogen content over non-limed rhizobia inoculated packages. In a field experiment, the adoption of soil test-based fertilizer application had an advantage of 25% in pod yield over farmers’ practice. Acid soil amelioration with lime improved pod yield from 14% to 39% over non-limed packages. Farmers’ field demonstration recorded the highest pod yield in the package where seeds were inoculated with S2 (RBHR-21) strain added with soil test-based fertilizers (STD) followed by STD + S1 (RBHR-15) with 98% and 84% increase over farmers’ practice. However, experimental evidence favored using both strains for bio-inoculation of the French bean crop.